KPT-PACE Generator: Executive Halal Professional Program - UiTM, Faculty of Business Management (UiTM, 2023)
The Executive Professional Program PENJANA KPT-PACE took place from August 20th to 27th, 2023. PENJANA KPT-PACE is a skills enhancement and competency strengthening program for final-year Halal students through professional certification based on expertise and competency in their respective fields. The program was inaugurated by the Dean of the Faculty of Business and Management, Professor Dr. Firdaus Abdullah. A total of 50 final-year students from semester 6 were selected to attend this professional program. The objective of this program is to provide a professional certificate that will add value to Bachelor of Business Administration (Hons.) Transport students. Additionally, the program aims to enhance the employability potential of students not only in the transportation and logistics industry but also in the halal industry and halal supply chain. This professional certificate is issued by the Department of Islamic Development Malaysia (JAKIM).